Responsiveness of the Indonesian Ombudsman in Handling Complaints about Maladministration of Police Services of the Republic of Indonesia - Abdul Mahsyar; Sitti Mukhlisa Kahar Musakkir; Sudarmi Sudarmi; Adnan Ma'ruf; Rijal Rijal (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The background of this research is the maladministration of Makassar Polrestabes services which can be seen in public complaints to the Ombudsman. The research problem is how responsive the handling of public complaints is. This study aims to determine the responsiveness in handling complaints in accordance with the provisions of the regulations. The approach used is a qualitative method with a phenomenological type, data obtained from informants namely the head and assistants of the RI Ombudsman Representative for South Sulawesi, Makassar Police Chief and staff, and the reporting community. Collecting data through interviews, observation and document review. The Miles and Huberman model interactive data analysis through the process of data reduction, data presentation, and inference/verification. The results of the study found three aspects of service responsiveness, namely input responsiveness, process responsiveness, and output responsiveness. All three have been carried out well based on work patterns that refer to applicable regulations. In the aspect of input responsiveness, the reporting community still complains because it is constrained by administrative and substantive requirements so that the report is not processed to the case register stage. Settlement of public complaints regarding maladministration of Makassar Polrestabes services is resolved with recommendations for clarification, mediation or conciliation, by providing understanding to the public on the service process. To increase responsiveness, the Ombudsman needs to carry out intensive socialization and assistance to parties affected by maladministration.